Preferences toward sports of students at the Faculty of Philosophy - Gošnik, Jelka (Array, 2003)
This survey was conducted with an intention to determine preliminary result on preferences toward sports of students at the Faculty of Philosophy, University of Zagreb. A survey group of 1681 students at the Faculty of Philosophy has ranked 62 sports on the scale from 1 to 5. Female students from 1st to 4th years and male students from the 1st to the 3rd years ranked swimming as the most preferred sport. Dance takes up the second place on the list of female students, while yoga and weekend field trip holds the third position. Male students tend to favor also table tennis, weekend field trip and backpacking. Wrestling and weightlifting are the least preferred sports to female students, while male students mostly keep away from synchronize swimming, rhythmic gymnastic and aerobics, i.e. sports that are perceived as feminine.